Features of realization values of condition at the level of predicative units (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article studies problem of typology and appurtenance condition of predicate to one or another part of speech, analyzed the variability of grammatical expression condition of semantics at the level predicative units.
Keywords: predicate; semantics; condition; adverb; verb